Ecological aspects of aquatic macrophytes for environmental pollution control: An eco-remedial approach - Santos, Jaqueline S.; Pontes, Montcharles S.; Arruda, Gilberto J.; Caires, Anderson R.L.; Lima, Sandro M.; Andrade, Luis H.C.; Bueno, Marcelo L.; Silva, Valéria F.B. da; Grillo, Renato [UNESP]; Santiago, Etenaldo F. (Elsevier, 2022)
Water resources are susceptible to various types of contamination that can directly affect the health of individuals, species and even entire communities. With human population growth, the increased demand for goods and services results in loss of water and soil quality. Given this scenario, the development of strategies for aquatic decontamination has been a matter of worldwide interest, and among many alternatives, phytoremediation has stood out as a natural, effective, and ecofriendly technology. In this sense, many species of aquatic macrophytes are described as decontaminators of organic and inorganic pollutants. In this chapter, we provide general and specific information on the ecological characteristics and biological mechanisms involved in the phytoremediation process by aquatic macrophytes. We also report some physical and chemical methods used to characterize, quantify, and monitor the removal of contaminants by these plants.
Keywords: Clean technologies; Contaminant removal; Eco-friendly technology; Phytoremediation; Water depollution